2018
DOI: 10.1080/14681811.2018.1475283
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s views on sexting education and support needs: findings and recommendations from a UK-based study

Abstract: Young people's sexting is an area of increasing concern amongst parents, educationalists and policy makers, yet little research has been conducted with young people themselves to explore their perspectives on the support they need to navigate relationships in the new digital media landscape. To address this absence, an inter-disciplinary team of researchers undertook a participatory study with students, aged 13 to 15, in a UK secondary school. This paper outlines key study findings, including young people's vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 26 publications
5
56
0
Order By: Relevance
“…Bindesbøl Holm Johansen et al 2019suggest that primary prevention of non-consensual image sharing needs to address how the violations are fuelled by gendered values and norms. The importance of discussing the nature of teenagers' sexting practises was also recognized by Jørgensen et al (2019). A key finding in their study is that the student participants repeatedly stated that they would like parents and teachers to talk to them about sexting practices using a more personal and relational communicative approach.…”
Section: Sexting Youth and Gendermentioning
confidence: 94%
See 2 more Smart Citations
“…Bindesbøl Holm Johansen et al 2019suggest that primary prevention of non-consensual image sharing needs to address how the violations are fuelled by gendered values and norms. The importance of discussing the nature of teenagers' sexting practises was also recognized by Jørgensen et al (2019). A key finding in their study is that the student participants repeatedly stated that they would like parents and teachers to talk to them about sexting practices using a more personal and relational communicative approach.…”
Section: Sexting Youth and Gendermentioning
confidence: 94%
“…The phenomenon of sexting -sending or receiving sexual images, videos or written messages with sexual content though the Internet or smartphones -has become an increasingly common practice among teens today (Barrense-Dias, Berchtold, Suris, & Akre, 2017;Jørgensen, Weckesser, Turner, & Wade, 2019;Madigan, Ly, Rash, Van Ouytsel, & Temple, 2018;Waling & Pym, 2019). Sexting can be a means of flirting or exploring sexuality, but the activity can also have negative consequences such as humiliation and harassment, especially if images are shared with others without the consent of the person depicted (Barrense-Dias et al, 2017;Cooper, Quayle, Jonsson, & Svedin, 2016;Madigan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Albury et al (2013), for example, found that young people distinguish between abusive sexting contexts characterised by violations of privacy and consent, and more positive contexts in which self-produced images are used for purposes relating to experimentation, bonding, trust, intimacy, and fun. Young people can be critical of what they perceive to be negative and judgmental sex education discourses (Jørgensen et al 2018). However, the tendency for young people to be risk averse and individualistic about sexting may be a result of their exposure to these institutional and cultural risk and harm discourses (Crofts et al 2015;De Ridder 2017.…”
Section: Young People's Perspectives On Sextingmentioning
confidence: 99%
“…As youth cultural perspectives likely vary between young people, further research that explores how young people construct meaning and how meaning works to provide a facilitating context to harmful sexting practices, as well as the power dynamics and social inequalities within this context, would be of value. Further research could also explore young people's perspectives on sexting education (see Jørgensen et al 2018) and how a rightsbased approach could practically be created and promoted.…”
Section: Limitations and Avenues For Future Researchmentioning
confidence: 99%